Titanium oxide nanotube arrays for high light extraction efficiency of GaN-based vertical light-emitting diodes. Issue 19 (28th April 2016) - Leem, Young-Chul; Seo, Okkyun; Jo, Yong-Ryun; Kim, Joon Heon; Chun, Jaeyi; Kim, Bong-Joong; Noh, Do Young; Lim, Wantae; Kim, Yong-Il; Park, Seong-Ju
Abstract : TiO2 nanotube arrays are fabricated on the surface of n-GaN through a liquid-phase conversion process using ZnO nanorods template for high-efficiency vertical light-emitting diodes. Abstract : TiO2 nanotube (NT) arrays were fabricated on the surface of n-GaN through a liquid-phase conversion process using ZnO nanorods (NRs) as a template for high-efficiency InGaN/GaN multiple quantum well (MQW) vertical light-emitting diodes (VLEDs). The optical output power of the VLEDs with TiO2 NTs was remarkably enhanced by 23% and 189% at an injection current of 350 mA compared to those of VLEDs with ZnO NRs and planar VLEDs, respectively. The large enhancement in optical output is attributed to a synergistic effect of efficient light injection from the n-GaN layer of the VLED to TiO2 NTs because of the well-matched refractive indices and superior light extraction into air at the end of the TiO2 NTs. Light propagation along various configurations of TiO2 NTs on the VLEDs was investigated using finite-difference time domain simulations and the results indicated that the wall thickness of the TiO2 NTs should be maintained close to 20 nm for superior light extraction from the VLEDs.